Does Islamic Religious Education Matter? Its Contribution to Moral Development and Student Discipline in Primary Education - Rita Rosita; Masitowati Gatot; Umi Fatonah (Educational Researcher Journal, 2026)
The development of students’ moral character and disciplinary behavior has become a major concern in contemporary education. As an integral component of character education in Muslim-majority societies, Islamic Religious Education (IRE) is expected to foster moral values and promote positive behavioral outcomes among students. This study aimed to examine the contribution of Islamic Religious Education to moral development and student discipline in primary education. A quantitative correlational design was employed involving 40 students from Grades IV to VI at SDN Cihideung Ilir 01, Bogor Regency, Indonesia. Data were collected through questionnaires and documentation and analyzed using Pearson’s Product-Moment Correlation, t-test, and coefficient of determination analyses. The findings revealed that the implementation of Islamic Religious Education was perceived positively by students, with an achievement level of 84.56%. Moral development and student discipline were also found to be at favorable levels, achieving scores of 85.44% and 87.47%, respectively. Correlation analysis indicated a significant positive relationship between Islamic Religious Education and moral development (r = .426), as well as between Islamic Religious Education and student discipline (r = .498). Furthermore, Islamic Religious Education contributed 18.1% to the variance in students’ moral development and 24.8% to the variance in student discipline. These findings suggest that Islamic Religious Education plays a meaningful role in supporting character formation among primary school students, particularly in fostering moral values and disciplinary behavior. However, the moderate magnitude of the relationships indicates that character development is influenced by multiple factors beyond formal religious instruction. The study highlights the importance of strengthening religious education as an integral component of character education within primary school settings